Acute and Repeated Administration of NLX-101, a Selective Serotonin-1A Receptor Biased Agonist, Reduces Audiogenic Seizures in Developing Fmr1 Knockout Mice. (15th January 2023) - Tao, X.; Newman-Tancredi, A.; Varney, M.A.; Razak, K.A.
Highlights: Severe auditory hypersensitivity and seizures are seen in FXS and other ASD. Seizures were dramatically reduced in Fmr1 KO mice by a 5-HT1A agonist, NLX-101. The protective effects of NLX-101 were blocked by selective 5-HT1A antagonists. Repeated administration of NLX-101 did not reduce its anti-seizure activity. Targeting 5-HT1A receptors may reduce sensory hypersensitivity in FXS and ASD. Abstract: F ragile X S yndrome (FXS) is a leading known genetic cause of Autism Spectrum Disorders (ASD) and intellectual disability. A consistent and debilitating phenotype of FXS is sensory hypersensitivity that manifests strongly in the auditory domain and may lead to delayed language and high anxiety. The mouse model of FXS, the Fmr1 KO mouse, also shows auditory hypersensitivity, an extreme form of which is seen as a udiogenic s eizures (AGS). The midbrain i nferior colliculus (IC) is critically involved in generating audiogenic seizures and IC neurons are hyper-responsive to sounds in developing Fmr1 KO mice. Serotonin-1A receptor (5-HT1A ) activation reduces IC activity. Therefore, we tested whether 5-HT1A activation is sufficient to reduce audiogenic seizures in Fmr1 KO mice. A selective and post-synaptic 5-HT1A receptor biased agonist, 3-Chloro-4-fluorophenyl-[4-fluoro-4-[[(5-methylpyrimidin-2-ylmethyl)amino]methyl]piperidin-1-yl] methanone (NLX-101, 0.6, 1.2, 1.8 or 2.4 mg/kg, i.p.) was administered to Fmr1 KO mice 15 min before seizure induction. Whereas the 0.6 mg/kg dose was ineffective in reducing seizures, the 1.2, 1.8 and 2.4 mg/kg doses of NLX-101 dramatically reduced seizures and increased mouse survival. Treatment with a combination of NLX-101 and 5-HT1A receptor antagonists prevented the protective effects of NLX-101, indicating that NLX-101 acts selectively through 5-HT1A receptors to reduce audiogenic seizures. NLX-101 (1.8 mg/kg) was still strongly effective in reducing seizures even after repeated administration over 5 days, suggesting an absence of tachyphylaxis to the effects of the compound. Together, these studies point to a promising treatment option targeting post-synaptic 5-HT1A receptors to reduce auditory hypersensitivity in FXS, and potentially across autism spectrum disorders.